Effect of vitamin D on serum BDNF level in patients with hypothyroidism caused by autoimmune thyroiditis - I.I. Kamyshna (Mìžnarodnij Endokrinologìčnij Žurnal, 2022)
Background. Hashimoto’s thyroiditis is a chronic autoimmune disease of the thyroid gland caused by an increase in thyroid antibodies. A growing body of research suggests that patients with Hashimoto’s thyroiditis may suffer from cognitive impairment. Therefore, it is important to identify risk factors that contribute to the development of cognitive impairment in patients with autoimmune thyroiditis to diagnose them early and treat. Given that the influence of thyroid hormones on the brain is undeniable, and their deficiency leads to a variety of neurological complications, early diagnosis and treatment of neurological disorders in thyroid diseases is crucial for preventing further progression of these complications. The purpose of the study is to determine the effect of vitamin D on the level of brain-derived neurotrophic factor (BDNF) in blood serum of patients with hypothyroidism caused by autoimmune thyroiditis. Materials and methods. Twenty-eight patients with hypothyroidism caused by autoimmune thyroiditis were included in the study. The serum level of BDNF was quantified using a solid-phase enzyme-linked immunosorbent assay with a highly sensitive Human BDNF ELISA Kit (Elabscience®, United States, Catalog No E-EL-H0010) on E.I.A. Reader Sirio S (Seac, Italy). Results. In our study, the administration of vitamin D and L-thyroxine led to a 7.4-fold increase in BDNF levels (p < 0.001). In the group of patients who took only L-thyroxine, serum content of BDNF increased by 2.1 times. In patients who took cholecalciferol and L-thyroxine, the level of BDNF was 2.48 times higher compared to those who took only L-thyroxine (p < 0.001). Conclusions. A positive effect of vitamin D on the serum level of BDNF was found in patients with hypothyroidism caused by autoimmune thyroiditis. Treatment of these individuals using additional administration of cholecalciferol on the background of L-thyroxine proved to be more effective compared to the administration of L-thyroxine alone (p < 0.001).